2011
DOI: 10.1007/s11418-010-0501-y
|View full text |Cite
|
Sign up to set email alerts
|

New phenolic compounds from Meehania urticifolia

Abstract: A new phenylethanoid glycoside, rashomoside A (1), a new phenolic glucoside, rashomoside B (2), and a new shikimic acid derivative (3) were isolated from Meehania urticifolia together with 12 known flavones (4-15), three known phenylethanoid glycosides (16-18), and 13 other compounds (19-31). The structure of each of these compounds was elucidated based on the results of spectroscopic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…In another study, the neuroprotective effect of 121 on Aβ 25-35 -induced neurotoxicity in SH-SY5Y cells was investigated. A 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide (MTT) reduction assay showed that 20 and 30 µg/mL of 121 significantly blocked cytotoxic effects of Aβ [25][26][27][28][29][30][31][32][33][34][35] on cell viability and the result was also confirmed by calcein-AM staining assay through analysis of morphological nuclear changes and DNA fragmentation. Meanwhile, pretreatment with 20 µg/mL of 121 decreased the number of apoptotic cells and scavenged reactive oxygen species (ROS).…”
Section: Neuroprotective Effectsmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study, the neuroprotective effect of 121 on Aβ 25-35 -induced neurotoxicity in SH-SY5Y cells was investigated. A 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide (MTT) reduction assay showed that 20 and 30 µg/mL of 121 significantly blocked cytotoxic effects of Aβ [25][26][27][28][29][30][31][32][33][34][35] on cell viability and the result was also confirmed by calcein-AM staining assay through analysis of morphological nuclear changes and DNA fragmentation. Meanwhile, pretreatment with 20 µg/mL of 121 decreased the number of apoptotic cells and scavenged reactive oxygen species (ROS).…”
Section: Neuroprotective Effectsmentioning
confidence: 98%
“…It showed that 121 was an activator of NF-E2-related factor 2 (Nrf2) and inducer of HO-1 expression. Compound 121 attenuated Aβ [25][26][27][28][29][30][31][32][33][34][35] -induced neurotoxicity by induction of HO-1 via extracellular regulated kinase (ERK) and PI3K/Akt signaling [63]. Similarly, the neuroprotective effects of salidroside (123) following traumatic brain injury were mediated, at least in part, through activation of the PI3K/Akt signaling pathway [64].…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 8 was isolated as the methyl ester of 7, which might be an artifact after using MeOH. We isolated compounds 1, 2, 3, 5, 6, and 7 previously from Meehaniaurticifolia [22] or Monarda fistulosa [17]. Rosmarinic acid (1) is known to be a typical phenylpropanoid dimer from Lamiaceae, Boraginaceae, Apiaceae, Rubiaceae, and Plantaginaceae [23].…”
Section: Resultsmentioning
confidence: 99%
“…17) Compounds 1 and 3-10 were new ( Fig. 1), and 2 was isolated as a natural product for the first time.…”
Section: And 3-o-[β-d-xylopyranosyl-(1-6)-β-d-glucopyranosyl]-(3r)-1-mentioning
confidence: 97%